ODONTOID FRACTURES - Ganapathy, Sibhi; Ramakrishna T, Venkata; Gopal, Swaroop (International Journal of Research -GRANTHAALAYAH, 2018)
Odontoid fractures account for approximately 7-15% (1) of cervical spine fractures, and almost 60% of fractures involving the axis. Neurological involvement is seen in upto 25% pts (2), and the primary mortality rate is around 12% (2). The mean age of occurrence is 47 years, with 2 peaks. In younger individuals, the fracture usually occurs due to a high velocity injury. In the elderly, hyperextension of the head and neck during domestic falls is the most common mode of injury. These injuries are frequently missed in the elderly, and the mortality is higher as compared to younger patients.